Financial reporting comparability: evidence on the impact of ambiguity tolerance and accounting standard guidance. (5th October 2011) - Harding, Noel; Xu, Jin Shu
In this study, we investigate whether the provision of formal guidance in the interpretation of ambiguous principles-based accounting standard provisions contributes to, or detracts from, financial reporting comparability. Analysing judgments made by Chinese accountants working in Beijing, Shanghai, and Guangzhou, our results highlight that the presentation of comparable financial information is hindered by the presence of guidance. These results suggest that if national and international comparability is desired, standard setting authorities should exercise caution when incorporating guidance into accounting standards.